2020
DOI: 10.24815/jdab.v7i1.15402
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Corporate Governance as a Moderating Variable on Earnings Management and Carbon Emission Disclosure

Abstract: The purpose of this study is to examine the influence of earnings management on carbon emission disclosure with corporate governance as a moderating variable. The population was companies in the sector of industry and chemical, agriculture, energy, transportation listed on the Indonesia stock exchange (IDX). Based on the purposive sampling method, 12 companies were selected as the samples (60 firmyear observations). The data analysis technique used is the moderate regression analysis (MRA). The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 43 publications
2
18
1
4
Order By: Relevance
“…Managers believe that by meeting stakeholder satisfaction and creating a good impression on the social and environmental aspects, the suspicion and vigilance of stakeholders can be reduced. Prior et al (2008) research is supported by the results of Gavana et al (2017), Rosani & Santosa (2020) and Astari et al (2020) research which found earnings management has a positive effect on corporate social responsibility disclosure. Based on this explanation, a hypothesis can be proposed: H1: Earnings management has a positive effect on corporate social responsibility disclosure…”
Section: Earnings Management and Corporate Social Responsibility Disclosurementioning
confidence: 78%
See 4 more Smart Citations
“…Managers believe that by meeting stakeholder satisfaction and creating a good impression on the social and environmental aspects, the suspicion and vigilance of stakeholders can be reduced. Prior et al (2008) research is supported by the results of Gavana et al (2017), Rosani & Santosa (2020) and Astari et al (2020) research which found earnings management has a positive effect on corporate social responsibility disclosure. Based on this explanation, a hypothesis can be proposed: H1: Earnings management has a positive effect on corporate social responsibility disclosure…”
Section: Earnings Management and Corporate Social Responsibility Disclosurementioning
confidence: 78%
“…The board of commissioners is required to maintain integrity and ensure that the supervisory and advisory functions are carried out properly. There is a significant positive relationship between the board of commissioners and CSR disclosure (Liu & Zhang, 2016;Astari et al, 2020;Ratmono et al, 2021). Larger board sizes tend to carry out effective monitoring mechanisms and encourage disclosure, to reduce information asymmetry between management and shareholders (Buertey et al, 2019).…”
Section: The Moderation Role Of Corporate Governance Of the Influence Of Earnings Management On Corporate Social Responsibility Disclosurmentioning
confidence: 99%
See 3 more Smart Citations